IMPROVING STUDENTS’ ABILITY TO WRITE NARRATIVE TEXTS THROUGH THE ACCELERATED LEARNING APPROACH AT THE ELEVENTH GRADE OF MAS TPI MEDAN - Istati Assyufiah (Universitas Negeri Islam Sumatera Utara, 2026)
The aims of this research were to find out whether the Accelerated Learning approach improves students’ ability to write narrative texts at the eleventh grade of MAS TPI Medan in the 2019/2020 academic year; and to describe the process of teaching narrative texts through the Accelerated Learning approach at the eleventh grade of MAS TPI Medan in the 2019/2020 academic year. This research was conducted with the eleventh-grade students of MAS TPI Medan. It employed Classroom Action Research (CAR) using both qualitative and quantitative approaches. The subjects of the research were eighteen students of class XI MAS TPI Medan, consisting of eight male students and ten female students. The research was conducted in two cycles of action. Each cycle consisted of four meetings and two post-tests. The research data were obtained from qualitative and quantitative sources. Qualitative data were collected through observation, interviews, researcher notes, and documentation. Quantitative data were obtained through writing tests. To analyze the quantitative data, the researcher calculated the mean scores of the tests and compared the results of the pre-test, post-test I, and post-test II. Based on the results of data analysis, it was found that the students’ mean scores improved from the pre-test to post-test I and post-test II. The mean score of the pretest was 51.66, while the mean score of post-test I was 61.80 (19.62%), and the mean score of post-test II was 82.91 (60.49%). These findings indicate that the Accelerated Learning approach significantly improved the students’ ability to write narrative texts.